Sistem Pakar dalam Menganalisis Alergi Kulit Manusia dengan Metode Certainty Factor - Hafid Dwi Adha; S Sumijan; Gunadi Widi Nurcahyo (Jurnal Sistim Informasi dan Teknologi, 2021)
The skin is human’s outer sense, which servers as protection from bacteria, viruses, and solar flares, and as a sense. Skin may suffer from a variety of factors, one of which is allergies. Human skin allergies result from a pressurized immune system that humans normally react to certain substances, such as food, animal hair, or medicine. In addition to the three factors, a current of society giveslittle attention to skin allergies and lack of care or awareness is a trigger factor. Thus, the aim of this research is to analyze human skin allergies using the Certainty Factor method. By conducting interviews and observations on Rahmatan Lil ‘Alamin Clinic, Padang City, found 10 skin allergic kinds, 27 skin allergic symptoms, and 50 patients data. Those data are treated using the Certainty Factor method with stages to decisive symptom and allergic code, set the rule, set the weight, and calculate Certainty Factor score. In this research, it obtained test results at a percentage of a large 92% and the most allergic diagnosed is allergic dermatitis. By the test results inferable that expert system designed can be used to determine the diagnosis of human skin allergies.